Leadership Justice: Analysis of the quality of Hadith, Concept and Implementation in the Context of Modern Leadership - Siti Sumadiyah; Damanhuri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Leader Justice refers to the principles and practices of justice implemented by a leader in carrying out their responsibilities. It encompasses various aspects, including fairness in decision-making, treatment of subordinates, allocation of resources, and organizational policies. A leader who practices justice is considered fair, transparent, and treats all members equally. This research proposes a comprehensive analysis of leader justice by focusing on the quality of hadith, the concept, and its implementation in the context of modern leadership. The study aims to understand how Islamic teachings, particularly those found in hadith, shape the concept of leader justice and how this concept can be effectively implemented in the context of modern leadership. The research methodology includes a review of relevant literature on hadith, justice theories, and modern leadership. The findings of this research are expected to provide profound insights into how the values of justice in Islamic teachings can serve as relevant guidance for modern leaders in carrying out their duties fairly and ethically. This research is anticipated to make a positive contribution to our understanding of the connection between religious teachings, justice, and leadership in the contemporary era.